Study of disturbance dynamo effects at nighttime equatorial F region in Indian longitude - Kakad, Bharati; Tiwari, D.; Pant, T.K. (My University, 2011)
Post sunset height of F layer may significantly increase or decrease as compared to their monthly quiet time pattern due to superimposed disturbed time electric field associated with either disturbance dynamo (DD) or prompt penetration (PP) or combination of both DD and PP. In this paper, the effects associated with disturbed time eastward electric field causing upward movement of F layer in the post sunset hours are investigated. Ionosonde data recorded at dip equatorial station Trivandrum for the period of 1990–2003 are scaled to obtain the variation of h′F from 17-31LT. Effect of magnetic activity on h′F (DH) is obtained by subtracting monthly quiet time average of h′F from disturbed time h′F. The maximum enhancement seen in h′F i.e DHmax provides the quantitative estimate of maximum effect of magnetic activity at equatorial F region. Here 97 magnetically disturbed days with DHmax ≥ 80 km are studied. Geomagnetic activity index ap is used along with AE and attempt has been made to identify the effects associated with short and long term DD electric field. It is found that the duration of short and long term DD effects seen at equatorial F region decreases with increase in solar flux. However this dependence is not applicable close to early morning hours (≥ 05LT). Time delays required to produce maximum effect at equatorial F region during high solar flux are found to be 16–23 hrs (0.5–4 hrs) for long (short) term DD effects studied here.
Keywords: Trivandrum; Ionosonde; Equatorial F region